Aspekty e-learningu jako metody nauczania na przykładzie piotrkowskiej platformy e-learningowej - Sobestiańczyk, Tomasz (Wydawnictwo Politechniki Łódzkiej, 2011)
Celem artykułu jest przedstawienie e-learningu, jako nowoczesnej metody nauczania, scharakteryzowanie słabych i mocnych stron w oparciu o piotrkowska platformę dydaktyczna.

The paper presents the basic terms and functions of e-learning, its advantages and disadvantages and characteristic. The second part shows free, e-learning system: ‘‘Piotrkowska platform e-learningowa’’. E-learning comprises all forms of electronically supported learning and teaching. E-learning is essentially the computer and network-enabled transfer of skills and knowledge
Determinants of the e-learning of Piotrkow e-learning platform
Keywords: e-learning; metody nauczania; platforma dydaktyczna; e-learning; teaching method; e-learning platform